A highly [001]-textured Sb2Se3 photocathode for efficient photoelectrochemical water reduction. Issue 47 (22nd November 2019) - Zhou, Hongpeng; Feng, Menglei; Song, Kena; Liao, Bin; Wang, Yichang; Liu, Ruchuan; Gong, Xiangnan; Zhang, Dingke; Cao, Lingfei; Chen, Shijian
Abstract : The highly [001]-oriented Sb2 Se3 film exhibits an outstanding charge carrier transport efficiency and minimized recombination losses. It delivers a record high saturation hydrogen reduction photocurrent density of −25.4 mA cm −2 . Abstract : Anisotropic Sb2 Se3 is an emerging earth-abundant photocathode for photoelectrochemical water splitting. However, controlling the growth of the Sb2 Se3 film with optimal [001] crystallographic orientation is still the most challenging issue. Here, we successfully synthesized [001]-oriented Sb2 Se3 via a reliable and facile method. The [001]-oriented Sb2 Se3 film could provide an excellent carrier-migration efficiency. Consequently, we achieved a record-high photocurrent density of −20.2 mA cm −2 at 0 VRHE and a very high half-cell solar-to-hydrogen efficiency of 1.36% under 1-sun simulated solar illumination in a TiO2 /[001]-Sb2 Se3 photocathode. This work provides an effective strategy and important guidelines for rationally designing optoelectronic devices based on the [001]-oriented Sb2 Se3 film.